Candida antarctica lipase B catalyzes the regioselective esterification of ecdysteroids at the C-2 OH - B. Danieli; G. Lesma; M. Luisetti; S. Riva (Tetrahedron, 1997)
Immobilized Candida antarctica lipase B (Novozym 435) catalyzes the regioselective acylation of 20R-hydroxyecdysone (1a) and its congeners 2a, 3a and 4a at the C-2 OH in high yield and purity. (C) 1997 Elsevier Science Ltd.